Terapi Komplementer The Effect Of Swedish Massage Complementary Therapy On Lowering Blood Pressure In Pregnant Women - Dina Arianty; Laurensia Yunita; Nur Hidayah (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Hypertension is a health problem that is very common in society, can be found in adulthood. This disease is usually undetected and does not cause typical symptoms for sufferers, therefore this disease can be called the "Silent Killer". Hypertension during pregnancy is a type of disease that is often found in pregnant women, this disease can be a previous illness or as a disorder during pregnancy. Hypertension during pregnancy if left untreated can cause various complications. The complications in question include premature babies, childbirth bleeding, brain bleeding, seizures, induction of birth, impaired fetal growth and death of the mother and fetus. Swedish massage can lower blood pressure, the efficacy of the results of this therapy can improve blood flow in the body, control the parasympathetic nervous system, the endorphins released increase so that they can respond to a person's heart rate decrease. So that it can lower blood pressure. The aim of the study was to determine the effect of giving Swedish massage complementary therapy on reducing blood pressure of pregnant women in the working area of the Haruai Health Center. This research method uses a pre-experiment with a one-group pretest-posttest design. 16 samples used total sampling sampling. Then the observation sheet and digital sphygmomanometer as research instruments. The results of the study showed that there was an effect before and after the Swedish massage intervention was given, indicated by the significance value of the statistical test results of the paired sample t-test of 0.000. The conclusion in this study is that there is an influence between giving massage therapy and reducing blood pressure in pregnant women with hypertension.